Fabrication of Whispering Gallery Mode (WGM) microresonator using core-to-core alignment fusion splicer for high sensitive temperature sensor trough optimum coupling gap with high q-factor - Noorbahrin, Nur Aida Syahmina; Mohd Yahaya, Nadrahtul Aqilah; Azahan, Siti Nurul Fatihah; Yusof, Muhammad Khudhori; Mohd Farid, Sabrina; Mohd Asseri, Siti Nurfatinah; Apsari, Retna; Zulkifli, Mohd Zamani (Elsevier, 2025)
In this work, the fabrication of whispering gallery mode (WGM) microsphere resonators using core-to-core alignment fusion splicer and its application as temperature sensors by optimization of coupling gap is studied and demonstrated. The proposed WGMs microsphere resonators are fabricated using core-to-core alignment fusion splicing technique, and the optimum coupling gap to a tapered fiber is made. Two configurations of coupling gap were tested, which are the 0 µm coupling gap in which both microsphere resonator and tapered fiber contacted, and 10 µm coupling gap. The sensor with 0 µm coupling gap recorded a finesse and Q-factor of 42.792 and 16,069.688 respectively at a resonance wavelength of 1542.69 nm. The sensor with 10 µm coupling gap recorded a finesse and Q-factor of 1.111 and 659.997 respectively at a resonance wavelength of 1544.40 nm. The temperature sensitivity was calculated to be 14.9 pm/◦C, with a wavelength resolution of 6.7 ×10− 2 m◦C and figure of merit (FOM) of 0.11/◦C. The smaller gap resulted in a better sensitivity of the temperature sensor. The sensor has a substantial potential as a cost-effective, highly stable, and easy-to-fabricate. The proposed setup has been proven to be extremely sensitive to environmental changes, making them a highly potential alternative temperature sensor, further increasing their appeal for real world application